Nimbidiol protects from renal injury by alleviating redox imbalance in diabetic mice - Juin, Subir Kumar; Pushpakumar, Sathnur; Sen, Utpal (Frontiers in Pharmacology, 2024)
Introduction: Chronic hyperglycemia-induced oxidative stress plays a crucial role in the development of diabetic nephropathy (DN). Moreover, adverse extracellular matrix (ECM) accumulation elevates renal resistive index leading to progressive worsening of the pathology in DN. Nimbidiol is an alpha-glucosidase inhibitor, isolated from the medicinal plant, 'neem' (Azadirachta indica) and reported as a promising anti-diabetic compound. Previously, a myriad of studies demonstrated an anti-oxidative property of a broad-spectrum neem-extracts in various diseases including diabetes. Our recent study has shown that Nimbidiol protects diabetic mice from fibrotic renal dysfunction in part by mitigating adverse ECM accumulation.However, the precise mechanism remains poorly understood.The present study aimed to investigate whether Nimbidiol ameliorates renal injury by reducing oxidative stress in type-1 diabetes. To test the hypothesis, wild-type (C57BL/6J) and diabetic Akita (C57BL/6-Ins2 Akita /J) mice aged 10-14 weeks were used to treat with saline or Nimbidiol (400 μg kg -1 day -1 ) for eight weeks.Results: Diabetic mice showed elevated blood pressure, increased renal resistive index, and decreased renal vasculature compared to wild-type control. In diabetic kidney, reactive oxygen species and the expression levels of 4HNE, p22phox, Nox4, and ROMO1 were increased while GSH: GSSG, and the expression levels of SOD-1, SOD-2, and catalase were decreased.Further, eNOS, ACE2, Sirt1 and IL-10 were found to be downregulated while iNOS and IL-17 were upregulated in diabetic kidney. The changes were accompanied by elevated expression of the renal injury markers viz., lipocalin-2 and KIM-1 in diabetic kidney. Moreover, an upregulation of p-NF-κB and a downregulation of IkBα were observed in diabetic kidney compared to the control. Nimbidiol ameliorated these pathological changes in diabetic mice.Altogether, the data of our study suggest that oxidative stress largely contributes to the diabetic renal injury, and Nimbidiol mitigates oxidative stress and thereby protects kidney in part by modulating NF-κB signaling pathway in type-1 diabetes.